Cyclodialysis-Enhanced Trabeculectomy with Triple Ologen Implantation. Issue 1 (January 2016) - Dada, Tanuj; Sharma, Reetika; Sinha, Gautam; Angmo, Dewang; Temkar, Shreyas
Purpose: To describe a novel technique of trabeculectomy combined with cyclodialysis and Ologen implantation at 3 sites in cases with high risk for failure of trabeculectomy. Methods: Six eyes of 6 patients who had high risk for failure of trabeculectomy underwent cyclodialysis-augmented trabeculectomy with Ologen implantation at 3 sites using the described technique. Results: All the eyes achieved target intraocular pressure, which was maintained until 1 year of follow-up. One eye required bleb needling at 6 weeks postoperative follow-up. None of the eyes had any other intraoperative or postoperative complications. Conclusions: This novel technique of combining trabeculectomy with cyclodialysis augmented by Ologen placement at 3 locations appears to have encouraging short-term intraocular pressure control and may be adopted in eyes with risk factors for failure of conventional trabeculectomy.